Evaluation paraumbilical flap for coverage of forearm and hand defects - Chikte, Baliram; Goud, I. Raja Kiran Kumar (International Surgery Journal, 2017)
Background: To find out the reliability and dimensions of the pedicled paraumbilical perforator flaps to cover the compound defects of the forearm and hand. Methods: Twelve (12) patients with defects of hand, wrist, forearm and elbow are included in this study. The study period extends from August 2012 to February 2015. Patients were aged between 12-45 years. The detailed systemic examination of the patient and the local examination of the wound was carried out in all the patients. For the patients with burns, hemodynamic stabilization was done with appropriate fluid management and blood transfusions. The routine laboratory investigations were done. Results: It was a prospective study of twelve (12) cases was carried out in this study. Six men (50%) aged between 25-45 years were the commonly affected group, followed by three women (25%) aged between 35 - 40 years and three children (25%), two males and one female aged between 12-17 years. Most common cause of the defect was electrical burns in seven cases (58.33%) due to accidental contact with high tension live electrical wire while at work in adults. In children it was due to accidental contact with live electric wire while they were playing. Most common site of injury was found on forearm in seven cases (58.33%), out of which left forearm was injured in five cases (41.66%) and right forearm in two cases (16.66%), followed by wrist in 2 cases (16.66%), dorsum of hand in one case (8.33%) and elbow in two cases (16.66%). All the defects were compound in nature with exposure of the tendons and bones and they were devoid of paratenon and periosteum. Conclusions: This study conclude that the paraumbilical flap is useful flap for coverage of the upper limb defects involving the hand, wrist, forearm and elbow. A fairly large flap with dimensions as large as 18 x 13 cm can be harvested. The flap is reliable with flap survival rate of 91.66%, (11 cases). There is no need to isolate the vascular pedicle, and the dissection is quick and easy. The flap and the limb remain in an elevated position and there is minimal edema and congestion postoperatively. Although the donor site scar is not concealed, as in groin flap, majority of the patients accepted the donor scar as it got concealed under the traditional dress. Thus, this flap can become workhorse for the defects of hand, wrist, proximal forearm and defects around the elbow.